Could Archimedes have calculated π with sand and a stick? Poderia Arquimedes ter calculado π com areia e um bastão? - Dellajustina F.J.* (2014)
We propose three methods to numerically determine the value of one of the most famous and important mathematical constants, the constant π. We present a numerical method inspired by the original method of Archimedes, an experimental mechanical method that uses sand and a stick, and finally, from a model based on the idea of probability, the Monte Carlo method is used for the evaluation of π. The experimental apparatus is very simple and of low cost, which makes easy the use of the experimental method and its application in physics and mathematics courses at high-school level. © by the Sociedade Brasileira de Física.